Divide 583.2 by 48.6 to get your answer, 12 hours.
We start by finding the intercept of the line: what does y equal when x=0? and what does x equal when y=0?
• intercept in x
y = 12 + 2x
0 = 12 + 2x
-12 = 2x
-6 = x
• intercept in y
y = 12 + 2x
y = 12 + 2(0)
y = 12 + 0
y = 12
Now we find three more points giving y a value and finding x
y = 12 + 2x
2 = 12 + 2x
2-12 = 2x
-10 = 2x
-5 = x
y = 12 + 2x
6 = 12 + 2x
6 - 12 = 2x
-6 = 2x
-3 = x
y = 12 + 2x
14 = 12 + 2x
14 - 12 = 2x
2 = 2x
1 = x
Notice how I gave y even numbers as values since we would have to divide with 2 at the end.
Sol. {(-6,0)(0,12)(-5,2)(-3,6)(1,14)}
Answer:
n(AUB)=n(A)+n(B)–n(AnB)
n(AUB)=n⁰(A)+n⁰(B)+n(AnB)
Step-by-step explanation:
This is the formula i have learned. Hope this will help u. U can use them according the question type.
Answer:p=qbecause they are the same
Step-by-step explanation:
Answer:
a14 = -40,960
Step-by-step explanation:
The sequence has a first term of 5 and a common ratio of -10/5 = -2, so the n-th term is given by ...
an = a1·r^(n-1)
an = 5·(-2)^(n-1)
The 14th term is then ...
a14 = 5·(-2)^(14-1) = -5·2^13 = -5·8192
a14 = -40,960